Configurable Router Design for Dynamically Reconfigurable Systems based on the SoCWire NoC - Arash Farhadi Beldachi; Mohammad Hosseinabady; Jose Luis Nunez-Yanez (International Journal of Reconfigurable and Embedded Systems (IJRES), 2013)
New Field Programmable Gate Arrays (FPGAs) are capable of implementing complete multi-core System-on-Chip (SoC) with the possibility of modifying the hardware configuration at run-time with partial dynamic reconfiguration. The usage of a soft reconfigurable Network-on-Chip (NoC) to connect these cores is investigated in this paper. We have used a standard switch developed with the objective of supporting dynamically reconfigurable FPGAs as the starting point to create a novel configurable router. The configurable router uses distributed routing suitable for regular topologies and can vary the number of local ports and communication ports to build multi dimensional networks (i.e., 2D and 3D) with different topologies. The evaluation results show that the selection of the ideal router is different depending on traffic patterns and design objectives. Overall, the mesh network with a four local ports router offers a higher level of performance with lower complexity compared to the traditional mesh with one local port router.